2011
DOI: 10.1016/j.scitotenv.2011.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biologically-active chemical mixtures on fish in a wastewater-impacted urban stream

Abstract: Stream flow in urban aquatic ecosystems often is maintained by water-reclamation plant (WRP) effluents that contain mixtures of natural and anthropogenic chemicals that persist through the treatment processes. In effluent-impacted streams, aquatic organisms such as fish are continuously exposed to biologically-active chemicals throughout their life cycles. The North Shore Channel of the Chicago River (Chicago, Illinois) is part of an urban ecosystem in which >80% of the annual flow consists of effluent from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 67 publications
3
38
1
1
Order By: Relevance
“…3.-Severity of intersex condition in largemouth bass collected from the upper Illinois River Waterway, Illinois, USA during April-May 2014. The severity rank classification was described by Blazer et al (2007) where 1 was a testes section with a single oocyte, rank 2 were testes with multiple singular (i.e., not clustered) oocytes, rank 3 was defined by clustering of 2-5 oocytes, and rank 4 was identified by multiple clusters in multiple areas within the longitudinal section (Barber et al, 2011;Martinovic-Weigelt et al, 2013). However, this study represents the first documentation of intersex condition in largemouth bass from the upper IRW and, although we acknowledge the limitations of this study, we hope that this initial detection of the condition will serve as a catalyst for future research on the EDCs in the IRW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.-Severity of intersex condition in largemouth bass collected from the upper Illinois River Waterway, Illinois, USA during April-May 2014. The severity rank classification was described by Blazer et al (2007) where 1 was a testes section with a single oocyte, rank 2 were testes with multiple singular (i.e., not clustered) oocytes, rank 3 was defined by clustering of 2-5 oocytes, and rank 4 was identified by multiple clusters in multiple areas within the longitudinal section (Barber et al, 2011;Martinovic-Weigelt et al, 2013). However, this study represents the first documentation of intersex condition in largemouth bass from the upper IRW and, although we acknowledge the limitations of this study, we hope that this initial detection of the condition will serve as a catalyst for future research on the EDCs in the IRW.…”
Section: Resultsmentioning
confidence: 99%
“…Martinovic-Weigelt et al (2013) documented the widespread occurrence of EEs in streams flowing through Chicago, where annual discharge is composed primarily of WRP effluents. Additional studies have documented significant contaminant loading in fish tissues collected from the Chicago-metropolitan region (Ramirez et al, 2009;Barber et al, 2011;Schultz et al, 2013). In Chicago-area streams where EE concentrations were reported to be especially high (16-18 ng EE2/L water; Martinovic-Weigelt et al, 2013), Schultz et al (2013) documented intersex condition and elevated levels of vitellogenin (egg yolk protein) in male common carp Cyprinus carpio, pumpkinseed Lepomis gibbosus, and bluegill L.macrochirus raised in cages in affected creeks.…”
Section: Introductionmentioning
confidence: 99%
“…At least 6 sections from each organ (gonad, liver) were stained using standard hematoxylin and eosin techniques (Carson, 1996;Gabe, 1976) in a Leica Autostainer XL (Nussloch, Germany) similar to methods used in other histopathological studies (Barber et al, 2011;Kidd et al, 2007;Vajda et al, 2008). Sections were assessed by an experienced histologist (HLS) and ranked on semiquantitative scales (0-4) for vacuolization of the liver (0 -no vacuoles visible;1 -b5% of total area vacuolated; 2 -vacuoles small but throughout image b 25% of area; 3 -broad presence of large vacuoles 25%-50% of area; 4 ->50% of area vacuolated) and the presence/absence of eosinic staining/proteinaceous fluid.…”
Section: Histopathologymentioning
confidence: 99%
“…However, regardless of how small the amount of E2 is, aquatic organism would be able to survive though their internal function is not fully normal (Elnwishy et al, 2007). Thus, it was also suggested that it reduces hepatic sensitivity to growth hormone, peripheral production of insulin-like growth factor (Norbeck & Sheridan, 2011) in rainbow fish and vitellogenin induction, and a physiological response consistent with exposure to estrogenic compounds (Barber et al, 2011).…”
Section: On His Study On Rainbow Trout (Oncorhynchus Mykiss)mentioning
confidence: 99%